Virtual Field Trips Borobudur Temple Assisted with Songs in Stimulating Writing Skills of Descriptive Texts - Najia, Annisa Uli; Sutikno, Putri Yanuarita (JOLLT Journal of Languages and Language Teaching, 2024)
Writing skills are crucial to basic language skills. However, observations in the field indicate that students' descriptive text writing skills are still low, especially in the aspect of content or ideas. This limitation makes it difficult for students to develop ideas, so the text does not provide enough information and description of the object. Â With this problem, this study aims to investigate the effectiveness of the virtual media field trip to Borobudur Temple, assisted by songs, in stimulating descriptive text writing skills. This quantitative research uses a quasi-experimental method and a nonequivalent (pretest-posttest) control group design. The research sample consisted of 52 students, with IV A as the experimental class and IV B as the control class, with each class totalling 26 students. The sampling technique used nonprobability sampling with saturated sampling. In the experimental class, special treatment was given, a virtual field trip to Borobudur Temple with the help of songs. In contrast, the control class only used conventional media such as pictures. Research data was collected using test techniques pretest and posttest. Then, the data analysis techniques using independent sample t-test, with the results in Sig. (2-tailed) 0.00<0,05 showing a significant influence of the virtual field trip media at Borobudur Temple assisted by songs on descriptive text-writing skills. This learning media is effective for stimulating descriptive text writing skills because it can inspire students to develop ideas based on virtual field trips and increase vocabulary through song lyrics to be translated into descriptive text.Â 